2019
DOI: 10.3390/molecules24193605
|View full text |Cite
|
Sign up to set email alerts
|

In vitro Fermentation of Polysaccharides from Aloe vera and the Evaluation of Antioxidant Activity and Production of Short Chain Fatty Acids

Abstract: Soluble or fermentable fibre has prebiotic effects that can be used in the food industry to modify the composition of microbiota species to benefit human health. Prebiotics mostly target Bifidobacterium and Lactobacillus strains, among others, which can fight against chronic diseases since colonic fermentation produces short chain fatty acids (SCFAs). The present work studied the changes produced in the fibre and polyphenolic compounds during in vitro digestion of gel (AV) and a polysaccharide extract (AP) fro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 48 publications
1
18
0
1
Order By: Relevance
“…a plant species of long‐standing ethnomedicinal importance in Pakistan, has come to fore internationally as a food additive of prebiotic value (Nazirah et al., 2013) endorsed by leading global food regulatory authorities such as the Food and Drug Administration (FDA) of the United States (El‐Sayed & El‐Sayed, 2020). Not only is Aloe vera a cheaper and a more procurable source of prebiotics than those available in the market (Gullón et al., 2015), it is also especially enriched in prebiotic polysaccharides such as acemannan and fructans (Khangwal & Shukla, 2019; Tornero‐Martínez et al., 2019), the latter being a demonstrably better prebiotic than inulin (Quezada et al., 2017). The resulting amalgamation of Aloe vera and probiotics, fits the International Scientific Association of Probiotics and Prebiotics ISAPP consensual definition, of a synbiotic (Swanson et al., 2020), with the whole purportedly more beneficial than either of its constituent parts (Sanders & Marco, 2010).…”
Section: Introductionmentioning
confidence: 99%
“…a plant species of long‐standing ethnomedicinal importance in Pakistan, has come to fore internationally as a food additive of prebiotic value (Nazirah et al., 2013) endorsed by leading global food regulatory authorities such as the Food and Drug Administration (FDA) of the United States (El‐Sayed & El‐Sayed, 2020). Not only is Aloe vera a cheaper and a more procurable source of prebiotics than those available in the market (Gullón et al., 2015), it is also especially enriched in prebiotic polysaccharides such as acemannan and fructans (Khangwal & Shukla, 2019; Tornero‐Martínez et al., 2019), the latter being a demonstrably better prebiotic than inulin (Quezada et al., 2017). The resulting amalgamation of Aloe vera and probiotics, fits the International Scientific Association of Probiotics and Prebiotics ISAPP consensual definition, of a synbiotic (Swanson et al., 2020), with the whole purportedly more beneficial than either of its constituent parts (Sanders & Marco, 2010).…”
Section: Introductionmentioning
confidence: 99%
“… Aloe vera plant and chemical structure of its main components. Reproduced with permission from [ 12 ]. …”
Section: Figurementioning
confidence: 99%
“…The fenugreek containing diet influences gut flora containing lesser Escherichia and greater Lactobacillus concentrations (9). The SCFAs are considered candidates to necrotic enteritis prevention for many activities, in vitro studies showed that they exert antimicrobial and antioxidant efficacy on a wide range of pathogenic bacteria (13,31), favoring integrity of intestinal mucosal barrier (32) and modulate resistance to disease (33). Supplements containing SCFAs may modify the intestinal microbiota by acting as bacteriostatic and bactericidal (34).…”
Section: Serum Butyric Acid Concentrationmentioning
confidence: 99%